2004
DOI: 10.1002/hep.20142
|View full text |Cite
|
Sign up to set email alerts
|

HLA and cytokine gene polymorphisms are independently associated with responses to hepatitis B vaccination

Abstract: Variable immune responses to hepatitis B virus (HBV) infection and recombinant HBV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 57 publications
8
118
1
2
Order By: Relevance
“…After applying a permutation test for correction for multiple testing seven SNPs maintained their statistical significance (Table 2). Consistent with previous reports, 21 we detected a strong genetic association between host response to hepatitis B vaccine and the MHC locus on chromosome 6 (rs5000563, most significant combined P-value ¼ 5.6 Â 10 -10 ; OR (95%CI) ¼ 0.60 (0.52-0.71)). Up to 11 polymorphisms within this region, spanning over 1.3 Mb, showed significant association in the second stage.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…After applying a permutation test for correction for multiple testing seven SNPs maintained their statistical significance (Table 2). Consistent with previous reports, 21 we detected a strong genetic association between host response to hepatitis B vaccine and the MHC locus on chromosome 6 (rs5000563, most significant combined P-value ¼ 5.6 Â 10 -10 ; OR (95%CI) ¼ 0.60 (0.52-0.71)). Up to 11 polymorphisms within this region, spanning over 1.3 Mb, showed significant association in the second stage.…”
Section: Resultssupporting
confidence: 92%
“…Several reports have associated genetic variability in the HLA locus with host response to hepatitis B vaccine in different populations. [21][22][23] Consistent with those studies, we detected a strong genetic association with the HLA region in the current Indonesian population sample. Out of 64 genotyped SNPs within the HLA region, 16 showed nominally significant P-values in the first stage (Supplementary Table S1).…”
Section: Discussionsupporting
confidence: 91%
“…Briefly, it appears that alleles associated with high/normal response are: DRB1*01, DRB1*I1, DRB1*15, DQB1*0501, DPB1*0401 and DRPB1*0402; whereas alleles correlated with non-or poor response are: DRB1*03, DRB1*07, DQB1*02, DPB1*1101, DRB1*14, and DRQB1*020. The only HLA population-based study in individuals of African origin (other than the above twin study in Gambians) is that by Wang and colleagues who assessed vaccine-response genetics in an ethnically mixed US population comprising a large proportion of African-Americans (Wang et al, 2004). Non-response to vaccination was attributed to variants HLA-Cw*03, DRB1*07 and DQB1*02, whereas response was associated with DRB1*15 and DQB1*06 (all results adjusted for ethnicity and other covariates).…”
Section: Genetics Of Immunity Induced By Hbv Vaccinationmentioning
confidence: 99%
“…None of these are based on populations of native African origin. Wang and colleagues (Wang et al, 2004) studied a population of predominantly black African Americans and reported on a haplotype consisting of three IL4 SNPs (-1098G/T, rs2243248; -590C/T, rs2243250; and -33C/T, rs2070874) associated with good response to HBV vaccination, whereas those carrying a 4bp deletion in the IL12B promoter were shown to be non-responsive. In this sample HIV infection was also correlated with non-response to vaccination.…”
Section: Genetics Of Immunity Induced By Hbv Vaccinationmentioning
confidence: 99%
“…Polymorphic variants in HLA genes have been found to be associated or linked with AR to hepatitis B vaccine (Kruskall et al 1992), influenza vaccine (Gelder et al 2002;Poland et al 2008a), measles vaccine (Poland 1998;Poland et al 2008b), and BCG tuberculosis vaccine (van Eden et al 1983), among others. However, non-MHC or non-HLA genes-IL1B, IL4R, IL6, IL10 and TNF-have also been found to be independently associated with response to hepatitis B vaccine (Wang et al 2004). Interestingly, although measles, mumps and rubella vaccines are all attenuated live vaccines that are administered simultaneously, the responses induced by these vaccines are influenced differently by host genetics (Kimman et al 2007).…”
Section: Introductionmentioning
confidence: 99%